Cause-fit, positive attitudes and behaviors within hybrid colombian organizations - Román-Calderón, Juan Pablo; Odoardi, Carlo; Battistelli, Adalgisa (RAE - Revista de Administracao de Empresas, 2015)
Socially oriented ventures have provided livelihoods and social recognition to disadvantaged communities in different corners of the world. In some cases, these ventures are the result of Corporate Social Responsibility (CSR) programs. In Latin America, this type of undertaking has responded positively to unmet social needs. The social cause drives these organizations and their human resources and they give high value to organizational cause-fit. This paper presents empirical evidence of the effects of perceived cause-fit on several worker attitudes and behaviors. Psychological contract theory was adopted as theoretical background. Employees working in a hybrid (for-profit/socially oriented) Colombian organization created by a CSR program participated in the survey. Data provided by 218 employees were analyzed using PLS structural equation modeling. The results suggest the ideological components of the employee-employer relationship predict positive attitudes and cooperative organizational behaviors towards hybrid organizations.